The impact of the covid-19 pandemic on the financial performance of publicly listed companies / Chan, C.H, Wong, W.K and Au Yong H.N - C.H, Chan; W.K, Wong; H.N, Au Yong (2023)
This study assesses how the pandemic has affected the financial performance of Public Listed Companies (PLCs) in Malaysia, examining data from both pre-pandemic and post-pandemic periods. Our primary focus is on evaluating Return on Asset (ROA) as the dependent variable, with independent variables including Leverage, Dividend Per Share, Asset Growth Rate, Tobin’s Q, Net Profit, Size, and the presence of COVID-19. Our dataset comprises annual reports spanning six years, from 2017 to 2022. The data is obtained from Refinitiv and Investing.com. We gathered this data from a representative sample of eighty publicly listed companies in Malaysia, representing diverse sectors such as Financial Services, Consumer Products & Services, Industrial Products & Services, and Healthcare. We employed various statistical techniques, including EViews, Panel Data Regression, Fixed Effect Model (FEM), and Random Effect Model (REM) as regression models. Additionally, we conducted the Hausman Test to determine the most suitable regression model and conducted diagnostic tests. The findings of this study indicate that there is no significant correlation between the presence of COVID-19 and the ROA of publicly listed companies in Malaysia. The Asset Growth Variable consistently shows a positive coefficient, implying that higher asset growth rates among listed companies are associated with increased returns on assets. Interestingly, Net Profit is the only variable demonstrating a consistent relationship across all industries, highlighting its importance as a consistent driver of financial performance. The research sample included a limited number of public listed companies, and the number of variables considered was also restricted. The chosen six-year timeline may not fully encompass the comprehensive impact of COVID-19. The treasury departments of these public listed companies are gaining a thorough understanding of the profound effects of COVID-19. The Malaysian government is actively seeking to comprehend the pandemic's impact on the financial performance of various sectors in the country. Our analysis underscores the significance of asset growth and Net Profit as key factors influencing financial performance across industries. This is one of the earliest study comparing financial performance of public listed companies in Bursa Malaysia before and after COVID-19.